2010
DOI: 10.1177/014556131008900706
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Nasal Schwannoma Clinically Presenting as an Angiofibroma of the Nasopharynx

Abstract: Benign schwannomas of the nasal cavity are rare. When they do occur, their clinical presentation is variable, and some are fairly vascular. We report the case of a 17-year-old boy who presented with epistaxis associated with a unilateral nasal mass that extended into the nasopharynx. The tumor was removed via a transpalatal approach. In most such cases, a clinical diagnosis of angiofibroma is made. In this case, however, histopathologic examination identified the lesion as a schwannoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The search yielded 52 studies and a total of 71 patients, including this reported case. 1,2,7,9 -11,13 -58…”
Section: Discussionmentioning
confidence: 99%
“…The search yielded 52 studies and a total of 71 patients, including this reported case. 1,2,7,9 -11,13 -58…”
Section: Discussionmentioning
confidence: 99%